The Role of N‐Substituents in Radiationless Deactivation of Aminated Derivatives of a Locked GFP Chromophore. Issue 35 (19th September 2017) - Baleeva, Nadezhda S.; Zaitseva, Snezhana O.; Gorbachev, Dmitriy A.; Smirnov, Alexander Yu.; Zagudaylova, Marina B.; Baranov, Mikhail S.
Abstract : We report the creation of a novel group of the ABDI‐BF2 fluorescent dyes based on the conformationally locked GFP chromophore. We studied the intramolecular mechanism of radiationless deactivation of the ABDI‐BF2 fluorophore by introducing the various substituents at the nitrogen atom. The results of this study and our previous work allowed us to claim that in case of ABDI‐BF2 this deactivation is determined by the formation of the nonfluorescent internal charge transfer exited state with a planar quinoidal structure. The electronic effects have a greater impact on the radiationless deactivation than the conformation. Thus, the introduction of an electron‐donating group is more effective than the creation of rigid derivatives. The presented dyes are characterized by high fluorescence quantum yields and pH‐independence in the physiological pH range, making them promising candidates for a wide spectrum of fluorescence labeling applications. Abstract : Fluorescent dyes based on aminated derivatives of locked GFP chromophores have been developed. Their properties indicate that the fluorescence quantum yield variation is determined by the formation of the nonfluorescent internal charge transfer exited state with a planar quinoidal structure. Thus, the electronic effects have a greater impact on the radiationless deactivation than conformation.